ANALISIS PENGARUH PRODUK HALAL TERHADAP LOYALITAS PELANGGAN DI INDUSTRI MAKANAN - Mitra Cahya Jaweda, Priya; Darmawan, Donny (Cross-Border Journal of Business Management, 2024)
This paper discusses the analysis of the influence of halal products on customer loyalty in the food industry. Halal products are becoming a major concern in the food industry, especially with increasing consumer demand for products that comply with halal principles. This research aims to analyze the extent to which the presence of halal products influences customer loyalty. The research method used is a survey by distributing questionnaires to respondents who are consumers of halal food products. Data analysis was carried out using relevant statistical techniques. It is hoped that the research results will provide insight into the importance of halal products in building and maintaining customer loyalty in the food industry